Experiences of inequitable care among Afghan mothers surviving near-miss morbidity in Tehran, Iran: a qualitative interview study - Soheila Mohammadi; Aje Carlbom; Robabeh Taheripanah; Birgitta Essén (BMC, 2017)
Abstract Background Providing equitable maternal care to migrants is a seriously challenging task for hosting countries. Iran, the second-most accessed country for refugees from Afghanistan, has achieved maternal health improvement. However, Afghan women with near-miss morbidity faced pre-hospital delays and disparity in maternal care at hospitals. This study explores experiences of maternal care among Afghan women surviving near-miss morbidity to increase insight into healthcare improvements for migrants. Methods A qualitative study was conducted at university hospitals in Tehran, from April 2013 to May 2014. A total of 11 Afghan women and 4 husbands were interviewed when women recovered from near-miss morbidity that occurred around the childbirth period. Mothers were identified prospectively using the WHO maternal near-miss approach. Thematic analysis was used along with a data-driven approach to organize data guided by the 'three delays model' theoretical framework. Results Mistreatment in the form of discrimination and insufficient medical attention were key experiences. Participants commonly perceived poor women-professional communication and delays in recognizing obstetric complications despite repeated care-seeking. Financial constraints, costly care, lack of health insurance, and low literacy were experienced barriers to accessing care to a lesser extent. Non-somatic consequences of near-miss morbidity affected mothers and families for extended periods. Conclusions Near-miss survivors' experiences provided remarkable insights into maternal care of Afghans in Iran. The challenge for the health system and professionals is to provide equitable care with dignity and improve communication skills with caring attitudes toward ethnic minorities. Antenatal visits provide the best and most appropriate opportunities to tackle health illiteracy in Afghan women.